2007
DOI: 10.1158/1078-0432.ccr-06-2732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ductal Lavage and Random Periareolar Fine Needle Aspiration as Tissue Acquisition Methods in Early Breast Cancer Prevention Trials

Abstract: Purpose: Short-term phase I and phase II breast cancer prevention trials require tissue acquisition at baseline and after intervention to evaluate modulation of potential biomarkers. Currently used tissue acquisition methods include ductal lavage (DL), random periareolar fine needle aspiration (RPFNA), and core needle biopsy. The optimum method to retrieve adequate samples and the most accepted method by study participants is not known. Experimental Design: We compared RPFNA and DL as breast tissue acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
(33 reference statements)
3
22
0
Order By: Relevance
“…For their report, they combined the results of two pilot chemoprevention trials in which both ductal lavage and RPFNA were done as baseline tissue eligibility screening procedures in 86 women with a median age of 53 years. Their results in this largely postmenopausal cohort for whom both ductal lavage and RPFNA were attempted indicate that ductal lavage produces sufficient cells for cytomorphology analysis in 31% of women compared with 96% for RPFNA (14). The proportion with evaluable cytomorphology is lower than that reported by others for a mix of premenopausal and postmenopausal women (7, 9, 10, 15) but is within range of what others report for postmenopausal women (11).…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…For their report, they combined the results of two pilot chemoprevention trials in which both ductal lavage and RPFNA were done as baseline tissue eligibility screening procedures in 86 women with a median age of 53 years. Their results in this largely postmenopausal cohort for whom both ductal lavage and RPFNA were attempted indicate that ductal lavage produces sufficient cells for cytomorphology analysis in 31% of women compared with 96% for RPFNA (14). The proportion with evaluable cytomorphology is lower than that reported by others for a mix of premenopausal and postmenopausal women (7, 9, 10, 15) but is within range of what others report for postmenopausal women (11).…”
mentioning
confidence: 45%
“…In this issue, Arun et al (14) report that the efficiency of ductal lavage in producing evaluable benign epithelial specimens for chemoprevention trials in high-risk women is dramatically less than for RPFNA. For their report, they combined the results of two pilot chemoprevention trials in which both ductal lavage and RPFNA were done as baseline tissue eligibility screening procedures in 86 women with a median age of 53 years.…”
mentioning
confidence: 99%
“…The FNA procedure was carried out as previously described (11). Briefly, patients with previous history of breast cancer underwent the procedure in their intact opposite breast.…”
Section: Fna and Cytologic Evaluationmentioning
confidence: 99%
“…Arun et al [11] recently reported that the efficiency of RPFNA in producing evaluable specimens for chemoprevention trials in high-risk women is higher than for ductal lavage, making RPFNA a more practical option for breast cancer prevention trials. Still, the invasiveness of the procedures may preclude a role in population-wide screening of high-risk women that requires repeated harvesting of material.…”
Section: Ductal Lavage and Random Periareolar Fine Needle Aspirationmentioning
confidence: 99%